Photoelastic stress analysis assisted evaluation of fracture toughness in hydrothermally aged epoxies - G. Pitarresi; A. Toscano; M. Scafidi; M. Di Filippo; S. Alessi; G. Spadaro (Fracture and Structural Integrity)
The present work has investigated the fracture toughness of a model DGEBA epoxy system subject to Hidro-Thermal aging. A Photoelastic Stress Analysis technique has been implemented, showing the evolution of stresses arising throughout the water uptake process due to the non-uniform swelling of the material. Gravimetric and Dynamic Mechanical Thermal Analyses have further complemented the characterization, showing the onset of plasticization effects with aging. The correlation of all previous characterizations has allowed to conclude that an increase of KIC fracture toughness is obtained at the fully saturated condition. In particular Photoelasticity has also revealed the onset of relevant swelling induced stresses during the first stages of water absorption, leading to an increase of fracture toughness due to compressive stresses settling near the crack tip. A stress free condition is instead reestablished at the later stages of absorption, suggesting that the increased toughness of the saturated material is an effect of the modifications induced by aging on the polymer structure.